Report on Probability A - Aldiss, Brian W. (Brian Wilson), 1925-2017; Lancer Books (Firm) (New York : Lancer, 1968)
An ominous sequence unfolds when it is revealed that strangely intriguing Mrs Mary is being watched from her garden by a trio of strange characters - G, S and C - who are in turn being watched by another observer, who is being watched by a solitary figure on a hill in a third dimension, who is being watched by a group of men in New York, who are being watched by a clairvoyant's prying mind?
Mode of access: Internet.
Keywords: Science fiction